Mengurai Riset tentang Inisiatif Zakat Indonesia - Najiba, Sumayyah; Handoko, Luqman Hakim; Baehaqi, Ahmad (Fakultas Ekonomi, UIN Maliki Malang, 2025)
This study aims to analyze the bibliometric research on the Indonesian Zakat Initiative (IZI) indexed in Google Scholar. The research method used is bibliometric analysis and a Systematic Literature Review (SLR) with the PRISMA approach. Data was obtained through Publish or Perish (PoP) using the keywords